1989
DOI: 10.1111/j.1365-2958.1989.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the surface regions of Pseudomonas aeruginosa PAK pilin: the importance of the C‐terminal region for adherence to human buccal epithelial cells

Abstract: The adherence of non-mucoid Pseudomonas aeruginosa strains is believed to be mediated by the pilus, which consists of a single protein subunit of 15,000 Daltons called pilin. Ten antipeptide antisera were raised to map the surface regions of pilin from P. aeruginosa strain K (PAK). Only one of the antipeptide antisera to the eight predicted surface regions failed to react with PAK pili in direct ELISA. Five out of eight synthetic peptides representing the eight predicted surface regions reacted with anti-PAK p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…The value of the 1244 glycan at the pilin C terminus may be related to its proximity to the DSL, a structure that facilitates adhesion to host tissue by attachment to surface glycolipids (31). This structure, although exposed at the pilus tip, is at least partially buried between the subunits of the fiber shaft (32). We have previously shown that the glycan is located on the fiber surface where it attenuates the natural hydrophobicity of the pilus (47).…”
Section: Discussionmentioning
confidence: 99%
“…The value of the 1244 glycan at the pilin C terminus may be related to its proximity to the DSL, a structure that facilitates adhesion to host tissue by attachment to surface glycolipids (31). This structure, although exposed at the pilus tip, is at least partially buried between the subunits of the fiber shaft (32). We have previously shown that the glycan is located on the fiber surface where it attenuates the natural hydrophobicity of the pilus (47).…”
Section: Discussionmentioning
confidence: 99%
“…The residue to which the strain 1244 glycan is covalently attached is immediately adjacent to the type IV pilin-specific disulfide loop (DSL) region, a structure important in host glycolipid-specific binding (40). Lee et al (27) showed that the DSL is at least partially buried in the outer protein layer of the pilus shaft and is only surface exposed at the fiber tip. These results suggest that the pilin glycan might also not be present at the fiber surface or be surface expressed only at the pilus tip.…”
mentioning
confidence: 99%
“…22 Pili, however, have considerable antigenic variation between strains. 24 Bacteria also possess an array of other virulence factors, including nonpilus adhesins. 25 Some clinical isolates of P. aeruginosa from keratitis are reportedly nonpiliated.…”
Section: Pathogenesismentioning
confidence: 99%